Peningkatan Perekonomian POKDARWIS Melalui Life Skill Merajut di Kecamatan Hulu Kuantan - Zein, Nurhayati; Afrida; Sariah (Tasnim Journal for Community Service, 2025)
The present community is expected to have adequate life skills for the sake of the economic economic support. One way to grow life skills can be done by providing training or coaching. Pokdarwis economic improvement activities through Knitting Life Skill in Hulu Kuantan District using the ABCD method. The expected goal is to facilitate facilitating participants to communicate with the servant. The activity went smoothly and it was found that 25% of the participants were classified as very good, 70% at a good level, and 5% were categorized as less.